2018
DOI: 10.24095/hpcdp.38.7/8.01
|View full text |Cite
|
Sign up to set email alerts
|

Mental health indicators among pregnant Aboriginal women in Canada: results from the Maternity Experiences Survey

Abstract: Our study demonstrated that common predictors of PPD including anxiety, experiencing stressful life events during pregnancy, having low levels of social support, and a previous history of depression were consistent among non-Aboriginal women. However, with the exception of the number of stressful events among First Nations offreserve, these were not associated with PPD among Aboriginal women. This information can be used to further increase awareness of mental health indicators among Aboriginal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
(19 reference statements)
2
13
0
Order By: Relevance
“…Our results regarding the unique risks among Indigenous mothers for each EPDS cut-off suggest that using only one such cut-off might miss groups of Indigenous mothers, a consideration when screening for PPD. This result is supported by Nelson et al's 2018 study (Nelson et al, 2018), which used the MES data to compare the prevalence and risk factors for PPD within three groups of Indigenous mothers with non-Indigenous mothers in Canada (Nelson et al, 2018). The distinct risk factors for PPD that we identified for Indigenous mothers might relate to higher prevalence of mental health problems in the general Indigenous population in Canada and elsewhere (Bowen et al, 2014;King et al, 2009;Kirmayer et al, 2000).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our results regarding the unique risks among Indigenous mothers for each EPDS cut-off suggest that using only one such cut-off might miss groups of Indigenous mothers, a consideration when screening for PPD. This result is supported by Nelson et al's 2018 study (Nelson et al, 2018), which used the MES data to compare the prevalence and risk factors for PPD within three groups of Indigenous mothers with non-Indigenous mothers in Canada (Nelson et al, 2018). The distinct risk factors for PPD that we identified for Indigenous mothers might relate to higher prevalence of mental health problems in the general Indigenous population in Canada and elsewhere (Bowen et al, 2014;King et al, 2009;Kirmayer et al, 2000).…”
Section: Discussionsupporting
confidence: 74%
“…A recent analysis of the MES data found that the prevalence of PPD is higher among each of three groups of Indigenous mothers (First Nations off-reserve, Inuit, and Métis) compared to non-Indigenous Canadian-born mothers (12.9 %, 10.6 %, and 9.1 %, respectively, compared to 5.6 %). These differences became non-significant after adjustment for different risk factors (Nelson et al, 2018). However, neither the MES data nor other data have been used to compare prevalence and risk factors across immigrant, Indigenous and Canadian-born non-Indigenous population groups.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with a recent Canadian study (that was not eligible for this review) that showed that postpartum depression rates were higher in First Nations (12.9%), Inuit (10.6%), and Métis (9.1%) women compared to their non-Indigenous peers (5.6%). 57 Using the same data, another group reported that Indigenous women were twice as likely to have postpartum depression compared to their non-Indigenous peers (OR 2.11; 95% CI, 1.44 to 3.09). 58 However, previous meta-analyses on the mental health of Indigenous males and females of a wide range of ages living in the Americas, Australia, and New Zealand suggested that the prevalence of mental health problems is generally not increased relative to non-Indigenous groups, and in some cases, may even be lower.…”
Section: Discussionmentioning
confidence: 96%
“…In Canada, Indigenous women are more likely to experience PPD, and rates are as high as 15% to 30% (Nelson et al, 2018). Chronic stress during pregnancy (Kingston et al, 2012) and PPD are important topics when addressing Indigenous perinatal health disparities (Chen et al, 2015;Gilbert et al, 2015;Smylie, 2012;Smylie et al, 2010).…”
Section: A U T H O R I N F Omentioning
confidence: 99%